STUDY OF AUDIENCE ACCEPTANCE OF MANDALIKA CIRCUIT EVENT PROMOTIONAL ADVERTISEMENTS INVOLVING VISUAL POLITICIANS IN LOMBOK - Arifin, Imam Khoirul; Prasetyo, Bambang Dwi; Oktaviani, Fitri Hariana (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2024)
The phenomenon of visual branding in advertising is increasingly important because it affects the image and acceptance of politician officials, especially among millennials and Gen Z who are apathetic to politics. The use of local elements such as the Mandalika Circuit in advertisements by political officials is aimed at attracting young voters, but it is often less authentic and creates negative perceptions of politicians and promoted events. The research is important because of the gap between politicians' expectations of attracting young voters and the reality of their acceptance of ads that use certain branding elements. This study aims to determine the representation and acceptance of Millennials and gen Z people towards Mandalika circuit promotional advertisements involving visuals of officials or politicians. This research uses qualitative method with reception analysis theory owned by Stuart Hall. This study used focus group discussion (FGD) with 10 informants who saw advertisements and belonged to the Millennial and Z generations, using the purposive sampling method. Roland Barthes' semiotic analysis was used to determine the representation of advertisements, and compared with audience acceptance based on the results of focus group discussion (FGD) which was classified to obtain results using three hypothetical positions proposed by Stuart Hall. The conclusion of this study shows that the use of visuals of politicians' faces in promotional advertisements tends to be rejected by Millennials and Gen Z, who emphasize the separation between politics and sports. Millennials are generally skeptical of politicization in promotion, while Gen Z is more firmly opposed to politicization and demands integrity and ethics in political campaigns.